2015
DOI: 10.1038/srep14435
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutations in myostatin by zinc-finger nucleases result in double-muscled phenotype in Meishan pigs

Abstract: Myostatin (MSTN) is a dominant inhibitor of skeletal muscle development and growth. Mutations in MSTN gene can lead to muscle hypertrophy or double-muscled (DM) phenotype in cattle, sheep, dog and human. However, there has not been reported significant muscle phenotypes in pigs in association with MSTN mutations. Pigs are an important source of meat production, as well as serve as a preferred animal model for the studies of human disease. To study the impacts of MSTN mutations on skeletal muscle growth in pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
146
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 55 publications
5
146
0
Order By: Relevance
“…In the studies of Proudfoot et al (2015), Han et al (2014), Luo et al (2014), Crispo et al (2015), Wang et al (2015c), and Wang et al (2015a) several offspring were born that had the desired mstn knock-out. The animals were visually different from the wild type individuals with an obvious difference in muscle mass and a difference was also observed during histological comparison of the muscles Qian et al, 2015). Qian et al (2015) have also found changes in the structure of the skeleton and fat content in the meat.…”
Section: Site-directed Nucleases For Improvement Of Economically Impomentioning
confidence: 92%
See 4 more Smart Citations
“…In the studies of Proudfoot et al (2015), Han et al (2014), Luo et al (2014), Crispo et al (2015), Wang et al (2015c), and Wang et al (2015a) several offspring were born that had the desired mstn knock-out. The animals were visually different from the wild type individuals with an obvious difference in muscle mass and a difference was also observed during histological comparison of the muscles Qian et al, 2015). Qian et al (2015) have also found changes in the structure of the skeleton and fat content in the meat.…”
Section: Site-directed Nucleases For Improvement Of Economically Impomentioning
confidence: 92%
“…The animals were visually different from the wild type individuals with an obvious difference in muscle mass and a difference was also observed during histological comparison of the muscles Qian et al, 2015). Qian et al (2015) have also found changes in the structure of the skeleton and fat content in the meat. Apart from livestock species, SDNs were also used in fish.…”
Section: Site-directed Nucleases For Improvement Of Economically Impomentioning
confidence: 92%
See 3 more Smart Citations